Food waste reduction behavior of quick service restaurant consumers in Metro Manila - Peralta, Ma. Rojemicah Arnante (College of Home Economics, University of the Philippines Diliman, 2023)
The problem of food waste has received global attention due to increasing concerns not only because of food security and environmental problems but also because of social and economic issues. In fact, the food service industry is responsible for approximately one-fourth of the total food waste. This study expanded Ajzen’s Theory of Planned Behavior (TPB) as a theoretical framework to investigate the food waste reduction behavior of fast-food consumers in Metro Manila. An online survey was conducted on 155 fast-food consumers to assess their food waste behavior using a 7-point Likert scale. The collected data was analyzed through partial least squares structural equation modeling. The findings showed that the intention to reduce food waste determined the behavior to do so. Personal attitude is the strongest motivator of intention to reduce food waste, followed by perceived behavioral control, price consciousness, and subjective norm, respectively. The study provided valuable insights regarding how the findings relate to Filipino food culture and traditions. Moreover, it discussed possible interventions that can be implemented by fast-food restaurants, policymakers, and consumers. Overall, this suggests that Ajzen’s Theory of Planned Behavior, along with the additional price consciousness, is applicable in investigating the food waste reduction behavior of fast-food consumers in Metro Manila. For future studies, it is recommended to explore other constructs that could enhance the TPB and provide further insights into consumers’ behavior regarding food waste reduction.